Kyrgyz Country Case Study - Ibraeva, Gulnara (Washington, DC: World Bank, 2012)
Following the guidelines laid out in the TOR received from the World Bank, the Kyrgyz case study focuses on the impact of the transition process since the early 1990s, at institutional and societal level. It examines four topics: state provision of services (eg education, health); changes in labor markets and new opportunities for women; and changes in family formation and dissolution; and the role of NGOs and the state in these areas.